Numeric geochemical reaction modelling, incorporating systems theory and implications for sustainable development : study on East Rand basin acid mine drainage, Witwatersrand, South Africa - Hansen, Robert Neill (2015)
Thesis (PhD)--Stellenbosch University, 2014.